A hybrid magnetorheological elastomer developed by encapsulation of magnetorheological fluid - Anil Bastola (Journal of Materials Science, 2018)
A new hybrid MR elastomer was fabricated by encapsulating a magnetorheological fluid (MR fluid) within a UV-curable silicone elastomer. A strong magneto-deformation effect was observed where the hybrid MR elastomer changed its shape in the presence of a magnetic field. Furthermore, when a moderately strong magnetic field was applied, the elastic and damping properties of the hybrid MR elastomer changed obviously. The magnetic field strength, strain amplitude, strain rate, preload, and orientation of magnetic flux direction affected the behavior of the new hybrid MR elastomer. The hybrid MR elastomer also exhibited a higher MR effect when compared with conventional MR elastomer. The investigation also found that the combination of magnetic field strength and preload highly influenced the hybrid MR elastomer behavior. This MR fluid-encapsulated elastomer is expected to be a potential candidate for the tunable spring-damper element as well soft actuators.